Kedudukan Komisi Pemberantasan Korupsi Dan Kejaksaan Dalam Sistem Ketatanegaraan Indonesia - Kuswan Hadji; Kingkin Setyaningsih; Anugraheni Wardah Ulinnuha; Bemby Navita; Nabila Raihana; Maya Larissa (International Forum of Researchers and Lecturers, 2024)
The position of the prosecutor's office in the Indonesian constitutional system is a law enforcement agency whose role is as a prosecutor in the justice system, which is also related to the legal system. However, this is not stated in the 1945 Constitution of the Republic of Indonesia. The position of the Corruption Commission (KPK) in the Indonesian constitutional system is often discussed, the Constitutional Court decided differently on several occasions in its (KPK) decisions regarding the position of the Indonesian constitutional system in that system. The Constitutional Court once considered that the Corruption Eradication Committee (KPK) is an independent state institution that is not included in the executive powers of parliament and the judiciary.